Relationship between Social Behaviour and Academic Motivation among Undergraduate Students of Faculty of Education Ahmadu Bello University, Zaria, Kaduna State - Usman, Sulaiman Salihu (Darul Yasin Al Sys, 2024)
This study examined the Relationship between Social Behaviour and Academic Motivation among Undergraduate Students of the Faculty of Education, Ahmadu Bello University, Zaria, Kaduna State, Nigeria. The study was guided by two objectives and two corresponding research questions and hypotheses. Correlational survey research design was employed in the study. The population comprised 300 level undergraduate students of Faculty of Education of Ahmadu Bello University, Zaria, with a total of 2629 male and female of 2021/2022 Academic Session that were still in the programme in the year 2023, while the sample size consisted of 346 respondents. Data were collected using adopted questionnaires from Merrell (2002) School Social Behaviour Scale (SBSS). The scale consisted of 15 items measured on a 5-point Likert-Scale ranging from strongly agree, agree, undecided, disagree, to strongly disagree with a reliability coefficient of 0.861 using Cronbach's Alpha. While Academic Motivation Scale (AMS) was adopted from Kotera, Conway, and Green (2020). The scale consisted of 14 items, measured on a 5-point Likert-Scale ranging from strongly agree, agree, undecided, disagree, to strongly disagree with a reliability coefficient of 0.704 using Cronbach's Alpha. Data collected were statistically analysed using Pearson Product Moment Correlation Coefficient. The findings of the study revealed that undergraduate students of the Faculty of Education have high level of academic motivation as indicated by the mean of 45.94 as guided by the scoring procedure. There is significant positive relationship between prosocial behaviour and academic motivation r=.745 and p= .001; a significant negative relationship exists between anti-social behaviour and academic motivation r = -.674 and P = 0.002 among undergraduate students of Faculty of Education, Ahmadu Bello University, Zaria. The researchers recommended that educational psychologists, counsellors, lecturers and parents should encourage students to enhance academic motivation by creating a positive and supportive learning environment. Also, students should be taught and encouraged on how to practice pro-social behaviour by fostering positive relationships with peers and teachers, and promoting intrinsic motivation since it boosts academic motivation and should play a critical role in discouraging anti-social behaviour since it is having negative relationship on academic motivation.